Genetic Stability of Sexing Strains Based on the Locus swof Ceratitis Capitata - Delprat, María Alejandra (2002)
This report deals with the process of improving the stability of medfly, Ceratitis capitata, genetic sexing strains (GSS) based on the swmutation on chromosome 2. This gene affects the rate of development as well as the eye colour and iridescence. The improved sexing strains were produced by mapping swwith deletions and then inducing and screening for new translocations with breakpoints close to the marker. The stability was assessed in large populations over many generations. Twenty-two new Y-2 translocations were identified and polytene chromosome analysis was performed to locate breakpoints. The translocation strains were ranked according to the distance of their breakpoints from sw. The map position of swis region 20D on 2R. As data on the stability of the 22 strains accumulated, Cast191 was shown to be the most promising as no recombination between swand the male sex was found. After rearing the strain for 22 generations under semi-mass rearing conditions, with a population size of 15,000 adults and scoring 1000 flies per generation, only one such event was detected (estimated frequency = 3.1 × 10−6). Further tests are being carried out with this strain to assess its suitability as a genetic sexing strain for medfly Sterile insect technique (SIT).